2000
DOI: 10.1074/jbc.m909695199
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK and NF-κB Collaborate to Induce Interleukin-6 Gene Expression and Release

Abstract: In cardiac myocytes, the stimulation of p38 MAPK by the MAPKK, MKK6, activates the transcription factor, NF-B, and protects cells from apoptosis. In the present study in primary neonatal rat cardiac myocytes, constitutively active MKK6, MKK6(Glu), bound to IB kinase (IKK)-␤ and stimulated its abilities to phosphorylate IB and to activate NF-B. MKK6(Glu) induced NF-B-dependent interleukin (IL)-6 transcription and IL-6 release in a p38-dependent manner. IL-6 protected myocardial cells against apoptosis. Like IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
114
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(136 citation statements)
references
References 63 publications
(51 reference statements)
16
114
3
Order By: Relevance
“…TNF-a-mediated IL-6 induction occurs through TGF-b activating kinase 1 (TAK1) stimulation of NF-kB in which p38 MAPK acts as an activator of IkB kinases (Craig et al, 2000). TAK1 is a MAPK kinase kinase that can be activated by TGF-b and bone morphogenic protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-a-mediated IL-6 induction occurs through TGF-b activating kinase 1 (TAK1) stimulation of NF-kB in which p38 MAPK acts as an activator of IkB kinases (Craig et al, 2000). TAK1 is a MAPK kinase kinase that can be activated by TGF-b and bone morphogenic protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that IL-6 activation by IL-1b or TNF-a is mediated through the p38 MAPK pathway, and p38 MAPK participates in TGF-b1-induced gene expression (Hanafusa et al, 1999;Craig et al, 2000;Wery-Zennaro et al, 2000). Based on these reports, we explored whether the p38 MAPK signaling is involved in the TGF-b1-induced IL-6 expression in prostate cancer cells.…”
Section: Tgf-b1 Activates Il-6 Expression In Prostate Carcinoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…5), fosters cardioprotection from I/R injury in TG mice (36). Also, NF B, which is known to induce expression of several cardioprotective genes, such as inducible nitric-oxide synthase, cyclooxygenase-2, superoxide dismutase, and interleukin-6 (13,(42)(43)(44), might confer cardioprotection in MKK6 mice. It is interesting to note that Bcl-2 fosters NF B activation in cardiac myocytes (45), providing a potential linkage in the mechanisms by which these two signaling proteins mediate protection.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that the transmission of extracellular signals are mediated by a signaling network, rather than a single signaling pathway, and that many factors are involved in hypertrophic growth of cardiomyocytes, the growth of cardiomyocytes is likely the result of cooperation among many signaling pathways (54,55). For instance, recent studies showed that activation of the p38 pathway may contribute to NF-B transcriptional activity (55)(56)(57)(58), most likely through enhancing expression of NF-B target genes (56,58). Future studies are needed to explore the interplay between the NF-B and other signaling pathways and to elucidate the in vivo role of NF-B activation in cardiomyocyte hypertrophy.…”
Section: Inhibition Of Nf-b Activation Blocks the Hypertrophic Agonismentioning
confidence: 99%